Effect of Gaseous carburizing thermochemical treatment on tribological behavior of Ti–6Al–4V alloy (Fracture and Structural Integrity, 2021)
This study, concerns the improvement of the hardness and resistance to wear of the Ti-6Al-4V alloy surface by means of thermochemical treatment, for obtaining coatings on the Ti-6Al-4V alloy gives performance of resistance to wear phenomena. Three-thermochemical treatment time (2h, 4h, and 6h) was chosen for investigation of the effect of such treatment on this alloy. The hardness test under an indentation load of 50 gf with a Vickers pyramidal indenter revealed that the surface hardness is 335 Hv for the untreated samples. On the other hand the hardness reaches approximately 1500 Hv during gas cementation at 930 °C for variable times (2h, 4h, 6h) followed by quenching at 840 °C in an oil medium, which was accompanied by a significant improvement in wear resistance. The characterization of the modified surface layers was made by means of a microscopic analysis and by X-ray diffraction. The case-hardening made it possible to obtain a wear resistance greater than that of the alloy not treated, minimal loss of mass by dry friction and an improvement in roughness as well as a good coefficient of friction.
Keywords: Ti-6Al-4V; Tribological behavior; Carburizing; Wear; Hardness